Patterns of alcohol and drug consumption in health care professionals: a portrait of students of lato sensu courses in a public institution - Rocha, Patrícia Rodrigues da; David, Helena Maria Scherlowski Leal (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2015)
This was a quantitative, descriptive and exploratory piece of research conducted with 111 students of lato sensu Postgraduate courses in a public nursing faculty in the city of Rio de Janeiro. The aim was to describe and discuss the prevalence and patterns of alcohol and other drug consumption in health care professionals, as well as the ways in which the worker and the institution in which they are employed deal with this. Alcohol was the most commonly used drug, followed by psycho-active substances. Around 67.6% agreed that drug use in employees may be related to stress and/or working conditions. The issue of drug use in the workplace must, then be approached by promoting prevention programs and workers’ quality of life.